2023
DOI: 10.3991/ijet.v18i03.34919
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Quizlet Learning Tool in Learners' Lexical Retention: A Quasi-Experimental Study

Abstract: The integration of technologies into education, especially language learning, has become more prevalent in this information age. One of the widely used tools for supporting second language (L2) vocabulary acquisition is Quizlet. Despite its increased popularity, empirical research on the effectiveness of Quizlet in enhancing L2 learners' lexical retention is still limited. Furthermore, most works primarily used conventional statistical methods such as t-tests or ANOVA, which might generate errors of Type I and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This illustrates that implementing Flashcard World app was more effective than traditional methods of teaching Benlaghrissi and Ouahidi vocabulary. This finding, however, aligns with previous studies on the pedagogical potential of MALL applications as effective learning tools in vocabulary [7,8,20,21,22,23,24].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This illustrates that implementing Flashcard World app was more effective than traditional methods of teaching Benlaghrissi and Ouahidi vocabulary. This finding, however, aligns with previous studies on the pedagogical potential of MALL applications as effective learning tools in vocabulary [7,8,20,21,22,23,24].…”
Section: Discussionsupporting
confidence: 91%
“…These features make learning enjoyable while creating sets, adding cards to start studying, and practising. In this context, several studies through interviewing students reported that students who used MALL applications got better scores because MALL apps brought a fun and enjoyable learning atmosphere [24,26,27]. One more explanation could be the game-like activities of Flashcard World application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations